2014
DOI: 10.14573/altex.1311152
|View full text |Cite
|
Sign up to set email alerts
|

Controversial role of Gamma-Glutamyl Transferase activity in cisplatin nephrotoxicity

Abstract: Summary Nephrotoxicity of chemotherapeutics is a major hindrance in the treatment

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…However, more recent studies propose a different view. Fliedl et al [ 28 ] found that after inhibiting GGT expression through a specific inhibitor, the renal toxicity of cisplatin decreased. These findings are indicative of a relationship between cisplatin nephrotoxicity and GGT-mediated drug metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…However, more recent studies propose a different view. Fliedl et al [ 28 ] found that after inhibiting GGT expression through a specific inhibitor, the renal toxicity of cisplatin decreased. These findings are indicative of a relationship between cisplatin nephrotoxicity and GGT-mediated drug metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…They are further metabolized to a reactive thiol group which is highly nephrotoxic [68]. The fact that GGT is predominantly found at the apical surface of the proximal tubule’s epithelial cells make it a desirable and possible target for managing cisplatin associated nephrotoxicity [72].…”
Section: Cisplatin-induced Nephrotoxicitymentioning
confidence: 99%
“…However, deletion of organic anion transporters or the endocytic receptor megalin also attenuates cisplatin toxicity in mouse models 38,155 , suggesting that alternative modes of cisplatin uptake exist. Cisplatin is also a substrate for γ-glutamyltransferase (GGT), which is expressed by proximal tubules, but conflicting reports exist as to whether GGT processing attenuates or exacerbates cisplatin toxicity 63 . Cisplatin also shows general cytotoxicity at high doses, suggesting that nonspecific toxicity responses are possible.…”
Section: Characterization Of Cellular Modelsmentioning
confidence: 99%
“…These renal enzymes, especially CYP3A4 and CYP3A5 and UGT1A9 and UGT2B7, might facilitate drug detoxification and efflux 10,58,59 , which could lead to drug–drug interactions because substrates that inhibit these enzymes could cause other drugs to accumulate in the proximal tubule, thereby exacerbating their nephrotoxic effects 60 . In addition to their detoxifying effects, various studies have demonstrated that these enzymes can also bioactivate xenobiotics, potentially exacerbating their nephrotoxic effects 6163 . However, the degree to which renal biotransformation contributes to the nephrotoxic effects of pharmaceutical compounds in vivo is not yet clear.…”
Section: Characterization Of Cellular Modelsmentioning
confidence: 99%